MENINGKATKAN KETERAMPILAN MENULIS DAN KREATIVITAS SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) - Debi Servinta Br Perangin angin; Dian Kartika Sari; Mara Untung Ritonga; Wisman Hadi (CV. ALIM'SPUBLISHING, 2025)
Writing skills play an important role in students ' language development, especially at the elementary school level. However, many students have difficulty expressing thoughts and ideas in writing. This study aims to analyze the application of Cooperative Integrated Reading and Composition (CIRC) learning model in improving students ' writing skills and creativity. The Cooperative Integrated Reading and Composition (CIRC) learning Model was chosen because it can integrate writing activities and develop students ' creativity. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results showed that the application of Cooperative Integrated Reading and Composition (CIRC) model can improve students ' writing skills, seen from their ability to construct sentences and convey ideas more structured and effective. In addition, student creativity also increased, where students were able to organize ideas, as well as pour them in writing with the right word selection. The CIRC Model also encourages cooperation, critical thinking and student creativity. This study identifies several challenges in its application, so it is advisable to implement the CIRC model with good time management and effective classroom management strategies to achieve optimal results. This study concludes that the Cooperative Integrated Reading and Composition (CIRC) learning model is an effective approach to improve students ' writing skills and creativity in elementary school.